2019
DOI: 10.3390/ani9121137
|View full text |Cite
|
Sign up to set email alerts
|

Different Diets Change the Expression of Bovine Serum Extracellular Vesicle-miRNAs

Abstract: Simple Summary: Studies over the last decade have shown that cells can communicate with neighboring or distant cells through complex packets stuffed with selected proteins, lipids, and nucleic acids, called extracellular vesicles. The wrapped macromolecules are miRNAs, which play a central role in mediating the signal communication of creatural patho/physiological systems. Extracellular vesicle-miRNAs vary among species and different body fluids, such as milk, urine, saliva, cerebrospinal fluid and blood, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The process of bioinformatics analysis was conducted as we did before [17]. Brifely, the low-quality reads, 5 primer contaminants and poly (A) were removed from raw reads by Cutadapt (version 1.14) (https://cutadapt.readthedocs.io/en/stable/) and the sequences between 15 and 41 nt were retained.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…The process of bioinformatics analysis was conducted as we did before [17]. Brifely, the low-quality reads, 5 primer contaminants and poly (A) were removed from raw reads by Cutadapt (version 1.14) (https://cutadapt.readthedocs.io/en/stable/) and the sequences between 15 and 41 nt were retained.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…We previously demonstrated that the partial replacement of forage with NFFS in dairy cow diets could decrease the ratio of ruminal acetate to propionate, which might change the whole metabolism through energy supply, including milk synthesis [14]. Furthermore, we found that the NFFS diets influenced the expression of circulatory and milk EV-miRNA, with increased particle concentration of milk EVs [15,16]. Hence, this study hypothesizes that the replacement of forage with NFFS could change the cow milk EV-protein composition.…”
Section: Introductionmentioning
confidence: 90%
“…In a recent study, it was discovered that different diets could affect miRNA expression of bovine serum, and their potential influence on immunity was discovered as well. The findings suggested that one could use effective dietary strategies to interfere with the physiological state of animals [ 99 ].…”
Section: Development Of Mirnas As Biomarkers Of Diet Nutritional Stat...mentioning
confidence: 99%